Luminescent materials based on organic salts pyrolyzed at the silica surface - P. O. Kuzema; Yu. M. Bolbukh; V. A. Tertykh (Хімія, фізика та технологія поверхні)
Recently, specific carbon-based nanomaterials (quantum dots, CDs) became highly attractive due to their low toxicity, good biocompatibility, chemical inertness, high photostability and fluorescence. Doping with some heteroatoms was found to be an effective approach to improve their luminescence. Besides, using the surface of silica as a support might facilitate the nanodots formation and expand the application area of carbon-silica composites. Recent advancements in synthesis of luminescent silica/CDs composites revealed great potential of such systems in bioimaging, sensor, as well as in solid-state lightning applications. Most of the synthetic methods are still relatively complex and costly. Here, the simple and inexpensive route to produce luminescent silica-based nanomaterials was used. The aim of this work was to study the luminescent properties of the materials obtained by pyrolysis of citric acid ureates at the nanosilica surface.